Removal of ammoniacal nitrogen from Malaysian palm oil mill effluent (POME) using optimized operating parameters of peat soil as natural adsorbent - Hossen, Md. Arif; Nurashikin, Yaacof; Fariha Najwa, Azahar; Noraziah, Ahmad; Azrina, Abd Aziz (Elsevier B.V., 2024)
Nowadays, the use of natural absorbents to remove pollutants from POME has gained remarkable attention. The main objective of this study is to investigate the suitability and performance of modified peat soil as an adsorbent for the removal of NH3-N from POME. The chemical activation method was performed using readily available NaOH for the first time to improve the adsorption performance of naturally available low-cost peat soil. The physical properties of raw and modified peat soil were determined using water-holding capacity, moisture content, bulk density, porosity, and BET surface area. The adsorbents were also characterized by SEM and FTIR to investigate surface morphology and chemical composition. To optimize the experimental parameters namely adsorbent dosage, agitation rate, and contact time for removal of NH3-N from POME, response surface methodology (RSM) was employed in this study with two different activation ratios. Substantial improvement of physical properties was attained after the modification of raw peat soil. The SEM images of modified peat soil showed a more porous space structure with larger voids while the FTIR demonstrated the distinctive functional groups in the raw and modified peat soil. At optimized conditions of 5.71 g/L adsorbent dosage, 50 rpm agitation rate, and 38.96 min contact time predicted removal efficiency of NH3-N has been revealed 64.06 and 58.74% at 1:20 and 1:30 activation ratios, respectively. The experimental investigation using optimized parameters showed 69.12 ± 2.5 and 61.57 ± 4.3% removal of NH3-N. The experimental and predicted results showed good agreement. The rapid removal of NH3-N (69.1% within 39 min) was achieved by chemically modified peat soil in this study compared to previously reported studies. Nevertheless, the raw and modified peat soil showed good stability up to three cycles of reusability.